Heavy Metal Accumulation in Soil-Wheat System of Coal Mining Area and Health Risk Assessment: A Case Study in Northern Anhui Province, China - Q. Li and S. B. Zhou (Nature Environment and Pollution Technology, 2020)
An investigation of 43 soil samples and their corresponding wheat samples collected from Qinan (QN) and Luling (LL) coal mining areas in Suzhou, China, was conducted to study the accumulation of heavy metals (Cu, Pb, Zn, Cd, Cr and Ni) in the soil-wheat system, and to evaluate the potential human health risk posed by heavy metals from long-term ingestion of local wheat. Results showed that Cu, Zn, Cd and Ni were accumulated in the soils from the two mining areas, higher proportions of all the investigated metals in residual fraction were recorded, while large amounts of Cd, Cu, Zn, Pb were also observed in the bioavailable or potential bioavailable fractions. Metal contents in the different parts of wheat mainly followed the order of Root>Stem>Grain. The trends of Bioaccumulation factor (BF) and Translocation factor (TF) values were Zn>Cd>Cu>Ni>Pb>Cr and Cu>Cd>Zn>Cr>Pb>Ni, respectively. Correlation analysis suggested that the accumulated metals in the grain were mainly supplied from exchangeable and carbonate bound fractions in soil. Since the health risk posed by heavy metals ingestion was very close to the maximum allowable limit, the safety of wheat consumption in the coal mining areas should be continually concerned.